SISTEM MONITORING DAN EVALUASI HAFALAN AL-QURAN DALAM UKM TAHFIDZ - Satriyo Yoga Pradana; Entin Martiana K; Ira Prasetyaningrum, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The Quran, as a miracle from Allah revealed to Prophet Muhammad SAW, holds a significant place in the lives of believers who are obliged to study, practice, and preserve its memorization. Quran memorization is prioritized in many educational institutions, including those offering special scholarships for memorizers. However, UKM Tahfidz Universitas Airlangga faces challenges due to the manual methods still used for tahfidz activities, such as recording student memorization in guidebooks and an inefficient program registration process. To address these issues, a web-based information system was developed to optimize the processes in UKM Tahfidz Universitas Airlangga. This system includes key features like monitoring Quran memorization through weekly reports with examiners and providing feedback in the form of grades and evaluations. With this system, both instructors and students can monitor memorization progress in real-time, allowing for more effective evaluation and guidance. The implementation of this information system has proven to increase efficiency, quality, and accuracy in the Quran memorization monitoring and evaluation processes. Additionally, the system supports scholarship requirements by ensuring that students meet the minimum memorization targets set. Overall, this system successfully enhances the effectiveness and efficiency of Quran memorization management at UKM Tahfidz Universitas Airlangga.